Sn(ii)-Mediated facile approach for the synthesis of 2-aryl-2H-indazole-3-phosphonates and their anticancer activities. (2nd June 2017) - Sudhapriya, N.; Balachandran, C.; Awale, S.; Perumal, P. T.
Abstract : The efficient synthesis of 2-aryl-2 H -indazole-3-phosphonates has been achieved successfully via a SnCl2 ·2H2 O mediated one-pot method. Abstract : A convenient three-component method was developed for the synthesis of various 2-aryl-2 H -indazole-3-phosphonates using SnCl2 ·2H2 O under conventional heating techniques. The transition metal free reaction, mild reaction conditions, one-pot operation, open flask conditions, wide substrate scope and good yields are a few important features of this methodology. This protocol proceeds with high atom economy via the formation of α-aminophosphonates followed by the generation of an indazole ring through N–N bond formation, eliminating water as a by-product. The cytotoxic properties of the 2-aryl-2 H -indazole-3-phosphonate derivatives were investigated against A549 and HepG-2 cells. Interestingly, compounds4d and4g showed potent cytotoxic properties against HepG-2 cells and compound4p showed significant cytotoxic properties against A549 cells. Intracellular visualization was done using a laser scanning confocal microscope. DNA fragmentation, colony formation, and apoptosis studies, flow cytometry and western blot analysis for4p against A549 cells have also been reported.